Anger, sadness and bear markets - Durand, Robert (Routledge Taylor & Francis Group, 2009)
Can an understanding of mood help us understand aspects of systematic risk, volume and portfolios’ exposure to systematic risk during bear-market regimes? We hypothesize that bear markets are associated with negative emotions: either a low-arousal negative state (e.g. sadness and depression)or a high-arousal negative state (e.g. anger and stress). We define a bear market as a stock market regime where the average return is statistically significantly lower than zero and find evidence that the bear market of November 1987 to February 1988 behaved as if it was associated with a pervasive low-arousal negative state amongst investors.